Family Planning in Taiwan : An Experiment in Social Change - Freedman, Ronald, 1917-2007; Takeshita, John Y. (Book collections on Project MUSE., 1969)
The experimental family planning program begun in 1963 in Taichung, the provincial capital of Taiwan, was the largest intensive program of its kind ever to be carried out for a sizable concentrated population. Its use of systematic observation and measurements was also unique. In evaluating the program and the data gathered, the authors seek to establish the extent to which the decline in Taiwan's fertility level resulted from the program rather than from the changes already underway in the society at that time. Finally, two vital questions occupy them: What has been learned in Taiwan, and how much of this can be applied to other developing countries with rapid population growth?Originally published in 1969. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.